Taxonomic update of the benthic marine brown algae (Phaeophyceae, Ochrophyta) from the Mexican Atlantic - García-García, Annie May Ek; Cabrera-Becerril, Ernesto; Núñez-Reséndiz, María Luisa; Dreckmann, Kurt M.; Sentíes, Abel (Instituto de Ecología, A.C., 2021)
Background and Aims: Except for the 2020 compilations for red algae and the phycoflora in Mexico, since the catalogs prior to 2001, no other studies have been carried out that involve the review and update of the status of brown algae in the Mexican Atlantic. The aim of this study was to integrate a list of brown algae from the Gulf of Mexico and the Mexican Caribbean in which all taxonomic updates from 2001 to date are considered. Methods: The specialized literature for the region published from 2001 to September 2021 and the database of the Herbarium UAMIZ were consulted for the integration of a phycofloristic list with distribution data. The synonymy and nomenclatural status of each name, as well as the classification system used, were reviewed in AlgaeBase. Key results: An updated list was obtained with 97 species and three infraspecific categories of brown algae, distributed in nine orders, 12 families and 39 genera. Of the total, from 2001 to the present, 41 correspond to additions to the flora, 24 are updated names, 10 are old records that have not been mentioned again and 25 continue to be recorded. Conclusions: The need to carry out floristic studies combined with molecular approaches it is evident, providing support for a more accurate and comprehensive knowledge of Mexican algal resources and making possible the incursion into ecological or biogeographic studies that allow the establishment of proposals for sustainable management or conservation.